Morphological study of the cranial bones of the Libyan fox (Vulpes rueppellii) in the north-eastern region of Libya - Youssef, Abdelgader K; Ahmed, Ahmed W; Darnawi, Neema A (Scientific Journal of University of Benghazi, 2021)
The cranial bones of a wild Libyan fox (Vulpes rueppellii) has been studied. The specimens were collected from different regions of Cyrenaica province. The skull was small and delicate, and the tympanic bulla was well developed. The dental formula was: I 3/3, C 1/1, P 4/4, M 2/3, total 42. Mental foramina and the angular process of the mandible were present.